Effects of gastrointestinal parasites on fecal glucocorticoids and behaviour in vervet monkeys (Chlorocebus pygerythrus) - Pooja Upadhayay; Colin A. Chapman; Gabriela F. Mastromonaco; Valerie A.M. Schoof (PLoS ONE, 2025)
Relationships between parasites, host physiology, and behaviours are complex. Parasites can influence host hormonal microenvironment and behaviour through “sickness behaviours” that generally conserve energy. Using a parasite removal experiment, we examined the effects of gastrointestinal parasites on fecal glucocorticoid metabolites (fGC) and behaviours of vervet monkeys (Chlorocebus pygerythrus) at Lake Nabugabo, Uganda. We collected parasitological, hormonal, and behavioural data from adult and subadult male and female vervets (N = 19) in 2014 across four study phases: pre-deworming, post-deworming, early reinfection, and late reinfection as well as in 2015. Overall, there was no decrease in fGC after deworming, but there was an increase following natural reinfection. There was no change in feeding across study phases; however, moving, grooming, and resting changed between the post-deworming and late reinfection phases, but not always in the predicted direction. Comparing behaviour across the same months in the following year as in the 2014 experimental study period, we found no differences in moving, feeding, grooming, and resting events. Despite behavioural variation between study phases, we cannot conclude that behavioural changes are due to parasitism rather than other seasonal variation. However, fGC increased following reinfection, which is consistent with parasitism being costly for hosts.